Language, gender and feminism theory, methodology and practice - Mills, Sara 1954- (Routledge, 2011)
Language, Gender and Feminism presents students and researchers with key contemporary theoretical perspectives, methodologies and analytical frameworks in the field of feminist linguistic analysis. Mills and Mullany cover a wide range of contemporary feminist theories and emphasise the importance of an interdisciplinary approach. Topics covered include: power, language and sexuality, sexism and an exploration of the difference between second and third wave feminist analysis. Each chapter presents examples from research conducted in different cultural and linguistic contexts which allows students to observe practical applications of all current theories and approaches. Throughout oral and written language data, from a wealth of different contexts, settings and sources, is thoroughly analysed. The book concludes with a discussion of how the field could advance and a overview of the various research methods, pertinent for future work in language and gender study. Language, Gender and Feminism is an invaluable text for students new to the discipline of Language and Gender studies within English Language, Linguistics, Communication Studies and Women's Studies, as well as being an up-to-date resource for more established researchers and scholars.